Yesus Sebagai Guru Teladan dalam Masyarakat Berdasarkan Perspektif Injil Matius - Talizaro Tafonao (UIN Sunan Gunung Djati Bandung, 2020)
In this paper, the author studies Jesus as a model teacher in a society based on the perspective of the Gospel of Matthew. This study departs from the author's observation of the condition of the teachers at this time, where educators today no longer make Jesus as the main role model in carrying out their teaching duties. The method used is a qualitative research method, the author studies the text of Matthew's gospel to analyze the Bible's view of Jesus as a model teacher. The analysis process carried out by the author is to use a variety of reliable library and electronic sources to support the analysis of the author. The results of this study found that Jesus is a model teacher for the community with indicators Jesus teaches through His real life, Jesus in teaching is not boring, Jesus always starts teaching from the way of thinking His disciples and Jesus always has a good relationship with students his disciples.